Pengaruh Ukuran Perusahaan, Profitabilitas, Dan Kepemilikan Instutisional Terhadap Ketepatan Waktu Penyampaian Laporan Keuangan (Studi Empiris Pada Perusahaan Properti Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2022) - Amelia, Mutiara Okta; Metalia, Mega (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Timeliness in submitting financial reports means that information must be submitted no later than 90 days after the date of the annual financial report in accordance with the 2022 Financial Services Authority (OJK) regulations to be used as a basis for assisting decision making and to avoid delays in decision making. This research aims to examine what factors influence the timeliness of submitting financial reports. The independent variables in this research are company size, profitability, and institutional ownership. The dependent variable in this research is the timeliness of submitting financial reports. The population of this research is 92 property and real estate companies listed on the IDX in 2018-2022. Sampling used the purposive sampling method. The statistical tool used is SPSS 25.